Greenhouse Gas Emissions from Stored Dairy Slurry from Multiple Farms. Issue 6 (1st November 2016) - Le Riche, Etienne L.; VanderZaag, Andrew C.; Wood, Jeffrey D.; Wagner‐Riddle, Claudia; Dunfield, Kari; Ngwabie, N. Martin; McCabe, John; Gordon, Robert J.
Abstract : A significant need exists to improve our understanding of the extent of greenhouse gas emissions from the storage of livestock manure to both improve the reliability of inventory assessments and the impact of beneficial management practice adoption. Factors affecting the extent and variability of greenhouse gas emissions from stored dairy manure were investigated. Emissions from six slurries stored in clean concrete tanks under identical "warm‐season" conditions were monitored consecutively over 173 d (18°C average air temperature). Methane (CH4 ) emissions varied considerably among the manures from 6.3 to 25.9 g m −2 d −1 and accounted for ∼96% of the total CO2 equivalent greenhouse gas emissions. The duration of the lag period, when methane emissions were near baseline levels, varied from 30 to 90 d from the beginning of storage. As a result, CH4 emissions were poorly correlated with air temperature prior to the time of peak emissions (i.e., the initial 48 to 108 d of storage) but improved afterward. The air temperature following the time of the peak CH4 flux and the length of the active methanogenesis period (i.e., when the daily CH4 emissions ≥ 7.6 g m −2 d −1 ) were highly correlated with CH4 emissions ( R 2 = 0.98, p < 0.01). Methane conversion factors (MCFs) ranged from 0.08 to 0.52 for the different manures. The MCFs generated from existing CH4 emission models were correlated ( R 2 = 0.68, p = 0.02) to MCFs calculated for the active methanogenesis period for manure containing wood bedding. A temperature component was added that improved the accuracy ( R 2 = 0.82, p < 0.01). This demonstrated that an improved understanding of lag period dynamics will enhance stored dairy manure greenhouse gas emission inventory calculations. Core Ideas: CH4 emissions and MCFs from six dairy slurries varied despite identical storage conditions. Postpeak CH4 emissions were more consistent among slurries compared with prepeak periods. CH4 emissions represented ∼96% of the overall GHG budget. N2 O emissions were low but represented an 8× greater portion of the GHG budget for tie‐stall than free‐stall systems.